EVALUATION OF THE APPLICATION OF GREEN CONSTRUCTION IN FACULTY OF ENGINEERING BUILDING, UIN CAMPUS 3 MALANG - Tauho, Victor Imanuel; Arystianto, Deni Putra (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2026)
The construction of buildings in Indonesia, especially in Batu City, East Java, one of which is the engineering faculty building on the campus of UIN Maulana Malik Ibrahim Malang - Campus 3 is one of the development projects that has the potential to become a pilot in the application of green building principles (BGH). Construction development often does not consider aspects of environmental sustainability. This research aims to evaluate the application of green construction principles in the project based on Permen PUPR No. 21 of 2021, especially at the construction implementation stage. The methods used include primary data collection through field observations and questionnaires to related parties (owner, consultant, and contractor), as well as secondary data from project documents. The analysis was conducted based on four main aspects in the BGH assessment, namely: suitability of construction implementation performance, green construction process, green behavioural practices, and green supply chain. The results of the research are expected to provide an overview of the level of implementation of green construction on the project as well as practical recommendations for improving its application. Thus, the engineering faculty building is expected to be an example of sustainable development in the higher education sector.